1994
DOI: 10.1111/j.1476-5381.1994.tb13097.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor responses after neo‐intima formation and endothelial removal in the rabbit carotid artery

Abstract: 1 The present study examined the responses of the rabbit carotid artery to five vasoconstrictors after neo-intima formation induced by perivascular collar treatment and evaluated the role of constitutive and inducible nitric oxide (NO) synthase and endothelial cells (ECs). 2 Ring segments of the rabbit carotid artery were mounted in organ chambers for isometric tension recording. Neo-intima-bearing vessels developed less force (Em,.) in response to KCl, the thromboxanemimetic U-46619 and 5-hydroxytryptamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
22
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
13
22
0
1
Order By: Relevance
“…10 Furthermore, in that study, it had also been reported that carotid arteries that had been collared for 7 days, but not control arteries, produced an increase in resting tone after addition of N G -nitro-L-arginine (10 Ϫ5 mol/L), suggesting a higher basal release of NO in collared arterial segments than in controls. 13 This confirmed our previous study, 25 which demonstrated that N G -nitro-L-arginine (2ϫ10 Ϫ5 mol/L) increased the contraction to KCl in collared arteries. However, this effect was seen only when ECs were present.…”
Section: De Meyer Et Al Periadventitial Inos and Intimal Thickeningsupporting
confidence: 89%
See 1 more Smart Citation
“…10 Furthermore, in that study, it had also been reported that carotid arteries that had been collared for 7 days, but not control arteries, produced an increase in resting tone after addition of N G -nitro-L-arginine (10 Ϫ5 mol/L), suggesting a higher basal release of NO in collared arterial segments than in controls. 13 This confirmed our previous study, 25 which demonstrated that N G -nitro-L-arginine (2ϫ10 Ϫ5 mol/L) increased the contraction to KCl in collared arteries. However, this effect was seen only when ECs were present.…”
Section: De Meyer Et Al Periadventitial Inos and Intimal Thickeningsupporting
confidence: 89%
“…However, this effect was seen only when ECs were present. 25 The discrepancy between these 2 studies may be explained not only by the absence or presence of ECs but also by the differences in the presence of remnants of periadventitial granulation tissue on the ring segments in the organ chambers.…”
Section: De Meyer Et Al Periadventitial Inos and Intimal Thickeningmentioning
confidence: 98%
“…Increased VSMC proliferation has been attributed to dysfunction of or damage to the endothelial lining in the area of intimal thickening and, more specifically, to decreased nitric oxide (NO) production. This effect is made evident by several studies in which NO donor agents or NO synthase gene transfer were shown to inhibit neointimal formation after balloon angioplasty in animal models (2)(3)(4). The effect inverse has been shown in studies where animals were subjected to balloon angioplasty and then treated with inhibitors of NO synthase (4).…”
mentioning
confidence: 77%
“…Yaka modelinin en karakteristik özelliklerinden biri de vasküler kasılma ve endotelyuma bağlı gevşe-me yanıtlarında meydana gelen değişikliklerdir (9,25) . Modelde endotelyum fiziksel bütünlüğünü koruması-na rağmen erken aşamada belirgin endotelyal disfonksiyon mevcuttur (9,26,27) .…”
Section: Discussionunclassified